Fatores críticos de sucesso em gestão de projetos orientados a mudanças de processos organizacionais - Idogawa, Juliano (2020)
Business process improvement is used by organizations looking to reduce costs, gain performance and as a competitive advantage. As consequence, projects for the implementation of business process management, from English Business Process Management (BPM), started to be carried out under different methodologies. The evolution of BPM happened in parallel with the evolution of project management. A common concern in both areas, success in projects, has become recurrent. Numerous studies present the critical success factors (CSF) for project management and for BPM, which corroborates this concern. This dissertation project proposes to measure the relations between the CSF of BPM and project management in a unified way. The selected methodology was based on quantitative analysis, consolidated from the structural equation modeling method. As a data collection instrument, it was decided to conduct a survey, solidified by established scales and with consistent psychometric properties. The expected contribution of this dissertation project encompasses both the academic and practical point of view when relating factors that can contribute to the success of these projects.